Technological developments in the Intelligent Transportation System (ITS) - Rachmat Suryadithia; Muhammad Faisal; Arman Syah Putra; Nurul Aisyah (International Journal of Science, Technology & Management, 2021)
The background of this research is to want to know the technological developments that exist in the intelligent transportation system, by knowing the developments it will be able to add to the repertoire of research and deepen similar research. The method used in this research is to conduct a literature review, by reading many journals that can be the basis for this research, reading will be able to develop the problems that have been researched. The problem raised in this research is wanting to know technological developments in the smart transportation system and making one example of a system that will be developed in smart transportation. This research will produce technological technologies that can be developed in smart transportation systems, and provide examples of research that can be developed on smart transportation systems.